On location-domination of set of vertices in cycles and paths - Exoo Geoffrey; Junnila Ville; Laihonen Tero; Ranto Sanna (Utilitas Mathematica Publishing Inc., 2022)
The motivation to study location-domination comes from finding
objects in sensor networks. In this paper, we consider
location-domination of both single vertices and sets of vertices in
cycles and paths. In many cases, optimal codes, i.e. codes with the
smallest cardinalities, are found.